English Language - Yohana, Maryetha Yova; Liestyana, Yuli; Utami, Yekti; Wahyuningsih, Tri; Oetomo, Hadi; Tugiyo, Tugiyo (Strata Business Review, 2025)
This research examines the influence of green creativity and MSMEs performance with green innovation as a mediating variable among MSMEs in Bantul Regency. The study population comprised MSMEs in Bantul Regency, with samples selected using nonprobability sampling through a purposive sampling approach. Data were collected via questionnaires from 56 MSMEs respondents. The relationships between variables were tested and analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM). The findings reveal that green creativity positively influences financial performance, although it shows no significant effect on environmental performance. However, the study demonstrates that green innovation positively and significantly mediates the relationship between green creativity and both environmental and financial performance. Regarding the implementation of green creativity, the author suggests that companies enhance the application of new environmentally friendly ideas to support sustainable environmental goals. SMEs are encouraged to continuously develop new ideas, such as combining materials with natural fibers in leather crafts or using leaves in the production of dyes.